2019
DOI: 10.1007/s40264-019-00891-6
|View full text |Cite
|
Sign up to set email alerts
|

The UK BIO-TRAC Study: A Cross-Sectional Study of Product and Batch Traceability for Biologics in Clinical Practice and Electronic Adverse Drug Reaction Reporting in the UK

Abstract: Introduction Due to the complexity of biologics and the inherent challenges for manufacturing, it is important to know the specific brand name and batch number of suspected biologics in adverse drug reaction (ADR) reports. Objective The aim of this study was to assess the extent to which biologics are traceable by brand name and batch number in UK hospital practice and in ADRs reported by patients and healthcare professionals. Methods We performed an online hospital pharmacist survey to capture information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies conducted in Latin America [15], Europe [22], and Australia [23], which aimed to determine the lack of inclusion of batch numbers in ADR reports, found that many prescribers did not have the information available at the time of reporting. A solution to this problem would be the education of HCPs on the importance of batch number inclusion in ADR reports and PMRs [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Latin America [15], Europe [22], and Australia [23], which aimed to determine the lack of inclusion of batch numbers in ADR reports, found that many prescribers did not have the information available at the time of reporting. A solution to this problem would be the education of HCPs on the importance of batch number inclusion in ADR reports and PMRs [17].…”
Section: Discussionmentioning
confidence: 99%
“…This may mean that the lack of use of batch numbers when dispensing or administering BMs may also indicate additional barriers to recording them in clinical practice. HCPs in other countries have expressed difficulty in recording batch numbers, some stating that electronic patient records do not have fields to include batch numbers [24], while others have stated that it is impractical to manually record batch numbers when dispensing and administering medicines [17]. This may also be the case at the selected hospitals where the study was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the need for traceability (e.g., the ability to trace which batch the patient has received despite the observation that, so far, differences in certain quality attributes between batches had limited impact on efficacy and safety). Previous studies have shown that the availability of the specific batch number in spontaneously recorded ADRs is generally low with percentages ranging between 0 and 20% 20,25 . Therefore, traceability needs improvement and several proposals have already been made 15,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the availability of the specific batch number in spontaneously recorded ADRs is generally low with percentages ranging between 0 and 20%. 20 , 25 Therefore, traceability needs improvement and several proposals have already been made. 15 , 26 Questions have, however, been raised about the cost‐effectiveness of improvement of traceability as tools for improvement place more pressure on the healthcare budget.…”
Section: Discussionmentioning
confidence: 99%